Перебіг зимової сплячки вечірниці рудої (Nyctalus noctula) залежно від чисельності групи (пілотне дослідження) - Vlaschenko, Anton; Moiseienko, Marharyta; Bohodist, Valeria; Domanska, Anastasia; Goltvyanskiy, Anatolii; Nahlov, Oleksandr (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2025)
This study investigated the inﬂuence of group size on the hibernation patterns of adult males of Nyctalus noctula during hibernation. Bats were divided into three categories (solitary, groups of six, and groups of sixteen) and nine experimental groups comprising one individual with temperature logger per group (iButton). Skin temperature (Ts) was monitored every ﬁve minutes. The results showed that bats in larger groups (the group of sixteen) entered longer and more stable torpor, with no instances of full arousal (Ts >20°C). In contrast, solitary bats exhibited more frequent arousals. All bats entered deep torpor after the ﬁrst nine days. No signiﬁcant diﬀerences in body mass loss were found between the groups. The ﬁndings highlight the importance of group size in reducing arousals during hibernation, and the role of social thermoregulation in conserving energy. Probl Cryobiol Cryomed 2024; 34(4):251–260